Comprehensive Study of Ambulance Technology Integration and Advancing Emergency Care and Transportation - ALSHAMMARI, ALI MOHAMMAD A; ALDHAFEERI, HAMOUD FAZZAA; ALOMANI, MOHAMMED FARAJ M; AL-MUTAIRI, HAMOD SANAT; ALSUBAIAI, MUBARAK SENAITAN; ALMUTAIRI, FAHAD SHDAID J; ALENZY, FAISEL GHAZY RASHD; ALSHAMMARI, MOHAMMED MEZAAL O; ALOBAIDAN, SULTAN MANOWER H; ALMUTAIR, ABDULELAH MATHKAR EID (Journal of Ecohumanism, 2024)
Introducing special technical equipment into ambulance services has led to the enhancement of emergency care and transport. Amid this process, this study attempts to uncover both the positive and negative effects, as well as the existing condition, of ambulance innovations on patient well-being, service organization, and EMS quality. GPS navigators and the use of real-time data transmission and telemedicine in moving intensive care units have contributed to relieving response times and better cooperation between emergency service personnel and medical facilities, as well as helping make urgent decisions at the scene. In this paper, an exploration of the technologies deployed in ambulance services, their advantages and disadvantages, and the future of EMS transportation has been done. This also provides an updated analysis of existing trends, emphasizing their consequences in the healthcare sphere worldwide.